The Prevention of The Hoaxes Spreads in Papua - Pujiyono Pujiyono; Pranoto Pranoto; Umi Khaerah Pati; Kukuh Tejomurti (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Students face the rapid development of information technology to have such a huge impact in the social aspect of society. In the midst of the covid pandemic, the use of social media is increasing so that the frequency of students exposed to hoax information and potentially become hoax spreaders is getting bigger. This research is normative research with socio-legal science approaches, By looking at how the law regulates phenomena or events that occur in society. The Ministry of Communication and Information of the Republic of Indonesia has established a method of tracking hoaxers and has arranged sanctions for perpetrators of hoaxes in the Information and Technology Law.